Strategi Adaptasi Nelayan Pesisir Cilamaya Wetan Dalam Meningkatkan Penghasilan Pasca Pembangunan Pltgu - Fahrullah, Fahrullah; Budiyanto, Eri; Nugraha, Kiky Aristiana; Purnamasari, Pupung (Jurnal Ilmiah Wahana Pendidikan, 2025)
The construction of the Steam Gas Power Plant (PLTGU) in Cilamaya Wetan has brought significant changes to the environment and economic activities of coastal communities, especially fishermen. This research aims to analyze the adaptation strategies applied by Cilamaya Wetan coastal fishermen in increasing their income after the construction of PLTGU. Researchers used a qualitative approach method with data collection through in-depth interviews, participatory observation, and documentation studies. The results showed that fishermen did not adopt various adaptation strategies. They did not switch to the aquaculture sector and did not receive technical training. In addition, fishermen do not utilize modern technology in fishing activities because the cost of such technology is very high. The study also found that collaboration between the government and non-government agencies in economic empowerment programs greatly supports the improvement of fishers' income. The findings of this study reveal the important role of innovation and external support in strengthening the economic resilience of fishermen against the impact of large infrastructure development such as PLTGU. Hopefully, these findings can serve as a reference for sustainable and equitable development policies for coastal communities.